Physicochemical and Microbial Characteristics of Anaerobic Granule Nuclei Developed by Cationic Polymer Additions under Syntroph Specific Substrate - Nasrul Hudayah (Science Faculty of Chiang Mai University, 2019)
This study aimed to build syntroph adapted-nuclei in a short period by concomitant early granulation and adaptation of seed sludge under a syntroph-specific substrate. Three UASB reactors – R1 (control-without polymer addition), R2 (dynafloc-synthetic polymer), and R3 (chitosan-natural cationic polymer) – were used. This strategy was successfully achieved in R3 (chitosan addition) on day 58. Chitosan decreased the negativity of microbial surface charges, as represented by the increased zeta potential from -26.4 mV at day 0 to -10.5 mV at day 58. The negativity of microbial surface charges in R1 and R2 slightly decreased to -24.5 mV and -22.2 mV on day 58, respectively. As a result, nuclei ratio and mean diameter size of microbial aggregates in R3 were significantly higher by approximately 55.1% and 115 µm, respectively, compared to those in R1 and R2, which then led to low SVI value. No significant difference in EPS production was found between the reactors, indicating that early granulation was mainly affected by the addition of cationic polymers, especially chitosan. However, microbial adaptation to the syntroph-specific substrate during the nucleation phase effectively increased specific activities of selected syntrophic microorganisms in all reactors. Microbial self-aggregation occurred in microbial aggregates of R1 due to the absence of cationic polymer additions. The microbial distributions, i.e., bacteria and Archaea, were well observed in aggregates of R3.